Legal protection children of Siri Marriage in Indonesia - Minan, Minan; Warka, Made; Hufron, Hufron (Technium Social Sciences Journal, 2022)
The founders on state have agreed that state protects the entire nation and entire homeland of Indonesia (Paragraph IV of Preamble to 1945 Constitution). The phrase protecting the whole nation has a very broad meaning, including protection against threats from within and from outside the country, as well as protection of human dignity as God's creatures. Such protection must be provided without distinction between men and women, young and old, as well as adults and children must receive the same treatment. The legal protection of civil rights children resulting from unregistered marriages is still very weak, because the Marriage Law does not regulate legal protection of children resulting from unregistered marriages. Whether or not there is legal protection must depend on recognition of biological father, or a notarial deed must be made.The struggle through the Padlan institution also has not given maximum results, because it only wins on paper, but it is not easy to implement. Therefore, it is necessary for state, with political will to make changes Marriage Law, which recognizes that children resulting from unregistered marriages have a civil legal relationship with their biological father.